Comparative assessment of Barthel index and functional independence measure in providing rehabilitation care for military personnel with combined injuries - Kostyantyn Babov; Alexander Plakida; Iryna Balashova; Iryna Zabolotna; Sergey Gushcha; Dmytro Bobylov (Фізична реабілітація та рекреаційно-оздоровчі технології)
In the structure of military traumatism, the number of multiple and combined wounds and injuries has increased significantly due to the expansion in the destructive properties of modern weapons. Establishing the correct rehabilitation diagnosis and subsequent stage-by-stage assessment of the results of rehabilitation therapy should be based on adequate functional assessment tools. The Barthel Index is the most widely used measure for assessing the ability to perform activities of daily living. However, recently, many authors have proposed using the Functional Independence Measure (FIM) for this purpose.